Investigation of a ceramic metal matrix composite functional surface layer manufactured using gas tungsten arc welding - Herbst, Stephan (Cranfield University, 2014)
Wear resistant surfaces with high toughness and impact resistant properties are to be created to improve the life cycle cost of brake discs for trains. A potential solution to this industrial problem is to use an arc cladding process. This work describes the application of gas tungsten arc welding (GTAW) for a structural ceramic Metal Matrix Composite (MMC) on steel. The structure of the two ceramics examined indicates the possibility of development of a wear resistant surface, which would extend the life of the brake disc. Silicon Carbide (SiC) and Tungsten Carbide (WC) ceramics were studied to embed them in a steel matrix by an advanced GTAW method. WC particles penetrated the liquid weld pool and also partially dissolved in the steel matrix, whereas, SiC because of the physical properties never penetrated deeper into the weld pool but segregated on the surface. Successful embedding and bonding of WC led to the decision to exercise an in-depth analysis of the bonding between the WC particles and the matrix. Chemical analysis of the matrix revealed more WC dissolution as compared to particle form within the clad. It was observed that WC reinforcement particles built a strong chemical bond with the steel matrix. This was shown by electron backscatter diffraction (EBSD) analysis. The hard clad layer composed of WC reinforced steel matrix gave an matching friction coefficient to high-strength steel in cold wear conditions through Pin-on-Disc wear and friction testing. A prototype railway brake disc was created with the established GTAW parameters to find out the difficulties of producing industrial scale components.
Keywords: Silicon carbide (SiC) ceramic; Tungsten Carbide (WC) ceramic; steel based clad layer; Tungsten Inert Gas welding (TIG)